3DMGAR: A Transient Quasi‐3D Point‐Source Green–Ampt Infiltration and Redistribution Model. Issue 1 (20th December 2018) - Gowdish, Leslie C.; Muñoz-Carpena, Rafael
Abstract : Core Ideas: Good design of point‐source irrigation systems needs simplified quasi‐spherical wetting models. Efficient irrigation with minimal impact, requires robust estimates of infiltration and redistribution. 3DMGAR is based on robust Green–Ampt infiltration and redistribution concepts for irrigation series. 3DMGAR tested favorably with benchmark 2D Richards simulations for a wide range of soils. Provided 3DMGAR source code is easy to apply and parameterize with readily available information. Although Richards' equation (RE) generally provides a good description of infiltration and water redistribution in soils, its numerical solutions can be computationally intensive or suffer from numerical instability and require extensive soil data. Simplified physically based approaches are often used in many practical settings after validation against RE used as a benchmark. The purpose of this research was to develop and test an approximated physical model for simulating transient point‐source infiltration and redistribution in a quasi three‐dimensional flow domain. An existing three‐dimensional Green–Ampt model that simulates only the infiltration phase is extended based on the one‐dimensional modified Green–Ampt with redistribution (MGAR) method to calculate the three‐dimensional soil water redistribution phase between point‐source events. Comparison with the HYDRUS‐2D numerical solution of RE showed the proposed model (3DMGAR) to provide satisfactory results for a broad range of soils. The ability of 3DMGAR to accurately and robustly simulate infiltration and redistribution for point‐source water application time series is particularly important for cases with difficult Richards solutions, such as in sandy soils, to improve water application efficiency and decrease chemical leaching in many settings like crop fertigation, waste water disposal, and mitigation of climate‐induced coastal salinization.